A dynamic model to evaluate the influence of the laying or retrieval speed on the installation and recovery of subsea equipment. (August 2018) - Tommasini, Rodrigo Batista; Carvalho, Leonardo de Oliveira; Pavanello, Renato
Highlights: A variable length cable-equipment model is proposed to analyze the installation and retrieval of subsea equipment. The model accurately predicts the dynamics of the system in comparison to an Orcaflex model. A variation of the static and dynamic loads on the system is predicted depending on the payout speed. The availability of the vessel changes as a function of the laying or hauling speed considered. The operations may be cheaper and safer if variable length models are used for the planning of the operation. Abstract: A new model for the dynamics of a cable-mass system representing the installation or retrieval of subsea equipment is analyzed. It considers a one-degree of freedom system, which is able to account for the variation of the cable's length during the time, simulating the equipment laying or recovering process. Also, the cable's mass is included in the analysis and the hydrodynamic forces are modeled by the Morison's equation. The resulting nonlinear equation of motion is integrated over the time domain via a predictor-corrector Newmark β -method. Firstly, the proposed model is compared with an Orcaflex model on fixed and variable length scenarios. The results show that the proposed model give accurate solutions in comparison with the finite element model through all the depths evaluated, even at zones where superharmonic response occurs. Secondly, the influence of payout speed on the dynamics of the system is assessed. Here, the system presents a variation on the static and dynamic forces, especially at the resonance zone. Finally, an operational weather window is generated for a specific case, which shows that the acceptable sea states change depending on the laying or retrieval speed considered. This highlights the importance of using models that account for the payout speed when analyzing subsea equipment installation and retrieval operations.